2009
DOI: 10.1002/cm.20359
|View full text |Cite
|
Sign up to set email alerts
|

TOGp regulates microtubule assembly and density during mitosis and contributes to chromosome directional instability

Abstract: TOGp, a member of the XMAP215 MAP family, is required for bipolar mitotic spindle assembly. To understand how TOGp contributes to spindle assembly, we examined microtubule dynamics after depleting TOGp by siRNA. Fluorescence recovery after photobleaching of GFP-tubulin demonstrated that spindle microtubule turnover is slowed two-fold in the absence of TOGp. Consistent with photobleaching results, microtubule regrowth after washout of the microtubule depolymerizing drug nocodazole was slower at the centrosomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 62 publications
(113 reference statements)
6
43
1
Order By: Relevance
“…We note that a pool of ch-TOG was retained at the spindle pole after TACC3 KS (supplementary material Fig. S1), which presumably corresponds to a functionally separate ch-TOG population, as previously described Cassimeris et al, 2009;Gergely et al, 2003). Since the discovery of clathrin as a binding partner of TACC3-ch-TOG, it has been debated whether TACC3-ch-TOG can operate independently of this complex Fu et al, 2011;Fu et al, 2010;Hubner et al, 2010;Lin et al, 2010;Royle, 2012).…”
Section: Discussionsupporting
confidence: 71%
“…We note that a pool of ch-TOG was retained at the spindle pole after TACC3 KS (supplementary material Fig. S1), which presumably corresponds to a functionally separate ch-TOG population, as previously described Cassimeris et al, 2009;Gergely et al, 2003). Since the discovery of clathrin as a binding partner of TACC3-ch-TOG, it has been debated whether TACC3-ch-TOG can operate independently of this complex Fu et al, 2011;Fu et al, 2010;Hubner et al, 2010;Lin et al, 2010;Royle, 2012).…”
Section: Discussionsupporting
confidence: 71%
“…Also in vitro studies have suggested that XMAP215 participates in the process of tubulin polymerization by binding to microtubule ends and catalyzing the addition of up to 25 tubulin dimers [Brouhard et al, 2008]. Since depletion of ch-TOG by siRNA in cells was shown to result in disorganized spindle poles and aberrant spindle morphologies [Gergely et al, 2003;Cassimeris and Morabito, 2004;Cassimeris et al, 2009], we can now confirm that such a phenotype is a result of a direct effect on microtubule dynamics. Most ch-TOG-depleted cells were indeed not able to assemble a functional spindle and remained blocked in mitosis (data not shown).…”
Section: Rnai Screen Of Candidate Mitotic Genes To Dissect Their Rolesupporting
confidence: 63%
“…During mitosis CLASPs are required for the incorporation and translocation/flux of microtubule subunits on kinetochore microtubules as well as to promote microtubule destabilization at kinetochores [Maiato et al, 2005;Maffini et al, 2009]. This is apparently counterintuitive for a family of proteins that promote microtubule stability during interphase [Galjart, 2005] but appears not to be an exception amongst classic microtubule-stabilizing proteins such as ch-TOG/XMAP215, which were also recently shown to induce microtubule destabilization at kinetochores [Cassimeris et al, 2009]. These findings suggest that the normal microtubule stabilizing role of CLASPs (and likely other kinetochore proteins) is being negatively regulated.…”
Section: Labile Versus Stable Kinetochore-microtubule Attachmentsmentioning
confidence: 99%